A comprehensive systematic review of leishmaniasis in patients undergoing drug-induced immunosuppression for the treatment of dermatological, rheumatological and gastroenterological diseases - Kurizky, Patricia Shu (2020)
Immunosuppression is an important risk factor for leishmaniasis. We assessed the clinical profile, geographic distribution and prevalence of leishmaniasis in patients undergoing immunosuppressive therapy for dermatological, rheumatological or gastroenterological autoimmune diseases. We identified relevant studies in PubMed, EMBASE, Scopus, Web of Science and LILACS on July 3rd, 2018. We included articles that reported at least one case of leishmaniasis in patients undergoing immunosuppressive treatment for dermatological, rheumatological or gastroenterological diseases. Our protocol was registered in PROSPERO (CRD42018103050). We assessed the quality of the included studies with the Joanna Briggs Institute Critical Appraisal Tool. After the removal of duplicates, 5,431 articles were collected and screened. We included 138 articles; the prevalence of leishmaniasis in six methodologically similar studies varied from three to 1,282 cases per 100,000 patients using anti-TNFα drugs, but the results were significantly heterogeneous . Leishmaniasis in patients treated with immunosuppressive drugs is a health problem mostly reported in European countries bordering the Mediterranean Sea; sporadic activities, such as travelling, seem not to be associated with a significant risk of leishmaniasis, although effective control measures must always be observed.